Effect of pomegranate extract (Punica granatum L.) on blood pressure and nitric oxide in gestational hypertension - Salsabila, Farah; Hadisaputro, Suharyo; Sunarjo, Lanny (MEDISAINS: Jurnal Ilmiah Ilmu-Ilmu Kesehatan, 2023)
Background: As a complication of pregnancy, uncontrolled hypertension will continue to be a complication that harms both mother and baby. Pomegranate peel, which contains high antioxidants, is potentially used as an antihypertensive of adjuvant pharmacological therapy. However, there has been no research on the effect of pomegranate extract in lowering blood pressure, so it is necessary to do related research. Purpose: Analyze the effect of pomegranate peel extract on blood pressure and nitric oxide levels in gestational hypertension. Methods: This is a quasi-experiment design pre-post-test with the control group. Through purposive sampling techniques, 32 respondents were divided into two groups. During 14 days, the intervention group received nifedipine 10 mg/day with 500 mg of pomegranate peel extract, while another group was only given nifedipine 10 mg/day. Results: The blood pressure of the intervention group decreased compared to the control group (p<0.05). Meanwhile, the nitric oxide level of the intervention group is increased compared to the control group (p<0.05). Conclusions: Pomegranate peel extract can reduce blood pressure and enhance nitric oxide levels in gestational hypertension.